Joint analysis of transcriptome and hormone metabolome on the mechanism of pruning effect on tea tree (Camellia sinensis) growth - Ye, Jianghua; Zhang, Qi; Shi, Lingshan; Wang, Yuhua; Li, Mingzhe; Chen, Yiling; Zhang, Ming; Chen, Jiaming; Chen, Meihui; Jia, Xiaoli; Xu, Chuanlan; Miao, Jia; et al. (Industrial crops and products, 2024)
Pruning is a vital agronomic strategy in the cultivation and management of tea trees, greatly affecting the growth of tea trees. In this study, the effect of pruning on tea tree growth was analyzed from transcriptome and hormone metabolome perspectives. The study concluded that pruned (SX) tea trees showed significant increases in leaf area, hundred bud weight, and yield, which were 31.82 %, 36.05 %, and 72.73 %, respectively, compared to unpruned (SC) tea trees. Analysis of gene differential expression and KEGG pathway enrichment showed that 1246 genes characterized by significant differences between SC and SX were significantly enriched in seven pathways, namely plant hormone signal transduction (ko04075), MAPK signaling pathway-plant (ko04016), biosynthesis of secondary metabolites (ko01110), plant-pathogen interaction (ko04626), alpha-linolenic acid metabolism (ko00592), metabolic pathways (ko01100), and ABC transporters (ko02010). Where all of the above pathways were significantly higher in SX than in SC, except for plant-pathogen interaction pathway. Analysis of hormone content showed that SX (21.53 ppm) had significantly higher hormone content than SC (18.85 ppm). Further analysis showed that six characteristic hormones differed significantly in SX, including significantly increased contents of L-phenylalanine and N-6-iso-pentenyladenosine-5′-monophosphate (iPAMP), and significantly decreased contents of indole, abscisic acid, jasmonoyl-L-isoleucine, and 12-hydroxyjasmonic acid in SX. In conclusion, the results showed that pruning stimulated gene expression of the ko04016 pathway, enhanced the strength of the ko01100 and ko01110 pathways, and increased the metabolism of the ko04075, ko00592, and ko02010 pathways, which then led to the increase of L-phenylalanine and iPAMP contents, and promoted tea tree growth. This study provides valuable insight into the importance of cultivating and managing tea trees, particularly those that have undergone pruning procedures. [Display omitted] •Pruning is an agronomic strategy that has a great impact on the growth of tea trees.•Pruning enhances gene expression of hormone signaling pathways in tea trees.•Pruning promotes the growth of tea trees by increasing the content of two hormones.